Large scale metrology - Scarr, A. J. (College of Aeronautics, 1963)
Introduction This interim note covers some of the problems encountered in the measurement of large sizes, up to 80 inches (200 mm), during investigations carried out at the College of Aeronautics. A description of a new design of stick micrometer for internal diameters and a micrometer frame for external diameters is included, together with experimental results obtained in using this equipment. Problems associated with measuring large sizes These may be classified under three broad headings:- a) The influence of temperature on the measurement b) Problems associated with the stiffness of the measuring equipment. (c) The elimination of operator feel. (a) The influence of temperature In practice, it may be extremely difficult to maintain both the component and measuring equipment at the internationally agreed standard of 20°C. Figure 1 shows the effect of variations in the temperature of steel components with respect to the Fundamental Tolerance value (B.S. 1916), expressed as a percentage of the tolerance grade. The particular case illustrated is for a 3°C. change in temperature on steel components, (coefficient of expansion assumed to be 11 parts in a million/°C), manufactured +o tolerance grade IT.6. It can be seen from this graph that in the smaller sizes up to say 10 inches (250 mm), the percentage of the tolerance taken up by the change in temperature remains relatively small, but with increase in size the effect of temperature becomes increasingly significant, until at 100 inches (2500 mm) 82% of the tolerance has been consumed.